The color of the Moon in visible light through a review of published photographs. A paradox? - Florides, Georgios A.; Christodoulides, Paul (My University, 2021)
Photographs are information sources and, as such, are used to provide evidence for many historical events. Such events were the lunar landing missions of the USA Apollo program in the end of 1960s and early 1970s. Many reels of film and video recordings have been made public to attest to the case, where in all the evidence provided, the moon surface is nearly devoid of strong colors and gray predominates. The present article addresses this issue by presenting images of the Apollo missions and assessing them through scientific knowledge that was available before or accumulated after the missions. Before the Apollo landings, observations from the Earth showed a red-brown color, agreeing with photographic evidence from orbits performed just before or just after the first Moon landing mission. New Moon missions provide contradicting evidence, as many photographs – in visible color – show a rather brown to red surface, not matching the Apollo observations. Particularly, three recent Chinese landing missions (2013-2020) show a consistent strong red brown color for the surface of the Moon, while missions from Japan and India show the gray surface of the Apollo missions. With the advancement of digital photography and relevant software, it is today easy to photograph the lunar color in visible light using relatively cheap equipment. Unfortunately, the result of using digital photography does not give a clear answer It is hence up to the space agencies that own the original photographic data to clarify the matter.
Keywords: Lunar surface color; Moon; Lunar soil; Apollo missions’ photography; Visible color